Погребение кочевника - Лобода, И.И. (Материалы по археологии, истории и этнографии Таврии, 2007)
В августе 1986 года во время проведения земляных работ на территории хозяйства «Магарач» в селе Вилино Бахчисарайского района было обнаружено
погребение кочевника. О находке было сообщено автору, в это время проводившему археологические раскопки курганов на территории вышеназванного хозяйства. Могила кочевника, как и исследовавшиеся курганы, находилась на высоком левом берегу реки Альма, в ее нижнем течении, на расстоянии 300 м к северо-востоку от курганов №№ 1 и 2. A burial of a nomad is described in the article; it was found in 1986, during earthworks on the territory of «Magarach» in the village of Vilino, Bakhchisarai district. On the bottom of a pit with rounded corners, there was a skeleton of a male, 40-45 years old, lying on the back, arms along the body, legs straight; his head was oriented to north-north-east. The burial was accomplished in a wooden box-coffin. Funeral equipment which remained intact till nowadays is limited by things which were to accompany the dead into the other world. They are: an iron knife, rings, arrow-heads, fire lighter, saddle-girth buckle, stirrups and bits, flint, rectangular bone plate with two holes, small copper vessel. Taking into consideration the details of funeral rite, set of objects accompanying a buried, their dating, the burial can be dated back to the 13th’ - 14th centuries.